Jewish identity and politics between the Maccabees and Bar Kokhba : groups, normativity, and rituals - Eckhardt, Benedikt. (Supplements to the Journal for the Study of Judaism, 2012)
The 300 years between the beginning of Maccabean resistance against Seleucid rule and the end of the Bar Kokhba revolt were formative for the development of Jewish identity in antiquity. The frequent political changes (from Seleucid to Hasmonean, Herodian and Roman rule) presented profound challenges to Jewish self-understanding. Political adjustments were coupled with internal reconfigurations. We witness the invention and reinterpretation of rituals, the emergence of new religious groups, and the use of scripture as argument. This volume brings together the perspectives of scholars of different background in order to make use of the multifaceted evidence. The interdisciplinary approach leads to a comprehensive picture of the interrelation between identity and politics in this crucial period of ancient Jewish history.